PENGARUH TINGKAT KESEHATAN BANK TERHADAP RETURN SAHAM PERBANKAN DI INDONESIA - Olivia Patricia (2021)
This research aims to analyze the soundness of the bank on the return of general banking stocks listed on the Indonesia Stock Exchange from 2015 to 2019. The sampling technique used in this study is the purposive sampling method. Based on the criteria of the predetermined sample, a total of 39 general banking companies was obtained. Data analysis in this study was carried out using Microsoft Office Excel 2010, and the hypothesis test using data regression analysis panel from E-Views program version 10.0 with a significance level of 5%. The results of this study are (1) liquidity risks as proxied by the Loan to Deposit Ratio (LDR) has a positive effect on stock returns; (2) good corporate governance has no effect on stock returns; (3) earnings are proxied by Return on Equity (ROE) has no effect on stock returns; (4) capital which is proxied by the Capital Adequacy Ratio (CAR) has a positive effect on stock returns.